Enhancing Students’ Learning Motivation through Project-Based Learning at MI Dangdeur - Andri Zainul Romdhoni; Nurnisaa; Sundarapandian Vaidyanatahan (Research Collaboration Community (Rescollacom), 2026)
This study aims to analyze the implementation of the Project-Based Learning (PjBL) method and its impact on students’ learning motivation at MI Dangdeur. This research employed a qualitative approach with a case study design involving fifth-grade and sixth-grade students, consisting of 18 and 21 students respectively. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of data analysis, including data reduction, data display, and conclusion drawing. The findings revealed that the implementation of PjBL was carried out through several structured stages, including the formulation of driving questions, project planning, implementation, monitoring, and evaluation. The results showed a significant improvement in students’ learning motivation across various indicators, such as persistence in completing tasks, enthusiasm in learning, initiative, collaborative participation, and sense of accomplishment. Students demonstrated higher engagement, active participation, and greater responsibility in the learning process compared to conventional teacher-centered methods. Furthermore, the study found that PjBL not only enhances students’ intrinsic motivation but also promotes collaboration, social interaction, and independent learning skills. Despite challenges such as limited time, differences in student abilities, and resource constraints, the overall implementation of PjBL proved to be effective in creating a more meaningful and student-centered learning environment. In conclusion, the Project-Based Learning method is an effective instructional approach to improve students’ learning motivation, particularly in primary education settings.